Perioperative Doppler ultrasound assessment of portal vein flow pulsatility in high-risk cardiac surgery patients: a multicentre prospective cohort study. (November 2022) - Denault, André; Couture, Etienne J.; De Medicis, Étienne; Shim, Jae-Kwang; Mazzeffi, Michael; Henderson, Reney A.; Langevin, Stephan; Dhawan, Richa; Michaud, Martin; Guensch, Dominik P.; Berger, David; Erb, Joachim M.; et al.
Abstract: Background: Portal vein Doppler ultrasound pulsatility measured by transoesophageal echocardiography is a marker of the haemodynamic impact of venous congestion in cardiac surgery. We investigated whether the presence of abnormal portal vein flow pulsatility is associated with a longer duration of invasive life support and postoperative complications in high-risk patients. Methods: In this multicentre cohort study, pulsed-wave Doppler ultrasound assessments of portal vein flow were performed during anaesthesia before initiation of cardiopulmonary bypass (before CPB) and after separation of cardiopulmonary bypass (after CPB). Abnormal pulsatility was defined as portal pulsatility fraction (PPF) ≥50% (PPF50). The primary outcome was the cumulative time in perioperative organ dysfunction (TPOD ) requiring invasive life support during 28 days. Secondary outcomes included major postoperative complications. Results: 373 patients, 71 (22.0%) had PPF50 before CPB and 77 (24.9%) after CPB. PPF50 was associated with longer duration of TPOD (median [inter-quartile range]; before CPB: 27 h [11–72] vs 19 h [8.5–42], P =0.02; after CPB: 27 h [11–61] vs 20 h [8–42], P =0.006). After adjusting for confounders, PPF50 before CPB showed significant association with TPOD . PPF50 after CPB was associated with a higher rate of major postoperative complications (36.4% vs 20.3%, P =0.006). Conclusions: Abnormal portal vein flow pulsatility before cardiopulmonary bypass was associated with longer duration of life support therapy after cardiac surgery in high-risk patients. Abnormal portal vein flow pulsatility after cardiopulmonary bypass separation was associated with a higher risk of major postoperative complications although this association was not independent of other factors. Clinical trial registration: NCT03656263.